COMPARATIVE ANALYSIS OF THE GROUNDS LEADING TO THE DISSOLUTION OF MARRIAGE WITHIN DIFFERENT EUROPEAN LAWS (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2020)
Divorce is one of the first legal institutions that people have been confronted with since ancient times, given that the family has always been at the foundation of society. However, not all spouses respect the obligations they have taken upon themselves once with the conclusion of marriage, so that, when the obligations can no longer be fulfilled by the parties, they must resort to a legal remedy that may lead to either the delay in the fulfillment of the obligations, of to the termination of legal relations on grounds not attributable or attributable to the guilty party, or to both parties, where applicable.Given that, depending on the specifics of the society to which they belong, the history of each state, the reasons leading to the dissolution of the marriage are different, the reasons found in the laws of European states differ. In this regard, in this study we aim to analyze the existing reasons in certain European states that may constitute grounds for divorce. Thus, the reasons leading to the dissolution of the marriage in Romania, France, and Italy shall be analyzed. We will note that the reasons are different, as well as the procedure that applies, being states in which the divorce procedure can be an administrative, notarial or judicial depending on the consent of the spouses at the dissolution of the marriage and/or whether there are minor children resulting from the aforementioned marriage.